Potential Bacillus anthracis Risk Zones for Male Bison in Southwestern Montana - Nekorchuk, Dawn M. (J Wildl Dis, 2018)
A re-emergence of anthrax, a zoonosis caused by the long-lived spores of Bacillus anthracis, occurred with a multi-species outbreak in southwestern Montana in 2008. It substantially impacted a managed herd of ~3500 free-ranging bison, Bison bison bison, on a large, private ranch southwest of Bozeman, with ~8% mortality and a disproportionate ~28% of mature males killed; a similar high rate occurred in male elk, Cervus canadensis. Grazing herbivores are particularly at risk for anthrax from ingesting spore-contaminated soil and grasses in persistent environmental pathogen reservoirs. We predicted areas of mature male bison habitat preference on the landscape using GPS collar data and a resource selection function model using environmental covariates. We overlaid preferred areas with ecological niche model-based predictions of B. anthracis environmental reservoirs to identify areas of high anthrax risk for male bison. Overlap areas were distributed across the ranch and not confined to pastures associated with the previous outbreak, suggesting that ongoing pasture exclusion alone will not prevent future outbreaks. Such data suggest vaccination campaigns should continue for bison and results can be further used to prioritize carcass surveillance in areas of greatest overlap.